Transient Antarctic Slope Current Response to Climate Change Including Meltwater - Ellie Q. Y. Ong; Matthew H. England; Edward Doddridge; Navid C. Constantinou (Geophysical Research Letters)
Abstract The future response of the Antarctic Slope Current (ASC) to projected transient changes in winds, radiative forcing, and meltwater input is examined in a high‐resolution ocean‐sea ice model. Meltwater changes are found to dominate the almost ‐circumpolar strengthening of the ASC. The strength of the ASC increases non‐linearly despite the linear meltwater perturbation applied, with a ∼14% increase in strength from 2000 to 2025 contrasting a ∼49% increase from 2025 to 2050. This non‐linear increase is, however, not seen in the coastal currents on the continental shelf. The non‐linear growth of ASC strength is attributed to meltwater accumulating on the continental shelf and poleward shifting warm waters north of the ASC, both triggered by reduced dense shelf water formation, and causing an accelerating ASC through thermal wind balance. Despite the strengthening ASC, any vulnerabilities in the current system could bring poleward shifted warmer waters onto the shelf, with implications for Antarctic ice shelf melt.